Hygroscopic aerosols amplify longwave downward radiation in the Arctic - D. Ji; M. Palm; M. Buschmann; K. Ebell; M. Maturilli; X. Sun; J. Notholt (Atmospheric Chemistry and Physics)
This study investigates the impact of hygroscopic aerosols, such as sea salt and sulfate, on longwave downward radiation in the Arctic. These aerosols absorb atmospheric water vapor, leading to wet growth, increased size, and enhanced longwave downward radiation emission, defined as the aerosol infrared radiation effect. Observations of aerosols, especially their composition, are challenging during the Arctic winter. We use an emission Fourier transform spectrometer to measure aerosol composition. Observations show that the aerosol infrared radiation effect of dry aerosols is limited to about 1.45±2.00 W m−2. Wet growth significantly increases this effect. During winter, at relative humidity levels between 60 % and 80 %, wet aerosols exhibit effects approximately 7 times greater than dry aerosols. When relative humidity exceeds 80 %, the effect can be up to 20 times higher. Sea salt aerosols in Ny-Ålesund demonstrate high effect values, while non-hygroscopic aerosols like black carbon and dust show consistently low values. Reanalysis data indicate increased water vapor and sea salt aerosol optical depth in Ny-Ålesund after 2000, correlating with significant positive temperature anomalies in this area. Moreover, wet aerosols can remain activated even in dry environments, continuously contributing high effects, thereby expanding the area affected by aerosol-induced warming. This warming effect may exacerbate Arctic warming, acting as a positive feedback mechanism.